Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/aoc.7222
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐sized Co(II), Ni(II), and Zr(IV) complexes of quinaldine‐based azo dye for promising therapeutic and catalytic applications: Synthesis, characterization, density functional theory studies and molecular docking

Abdalla M. Khedr,
Mohamed Gaber,
Mohsen Elsharkawy
et al.

Abstract: Novel azo dye containing the heterocyclic quinaldine nucleus, 3‐((2‐methylquinolin‐4‐yl)diazenyl)naphthalen‐2‐ol HL, and its Co(II), Ni(II) and Zr(IV) nano‐sized metal chelates have been synthesized and fully characterized by alternative analytical and spectral techniques. The finding indicated that the ligand coordinated as a monobasic bidentate via azo nitrogen and hydroxyl oxygen atom, resulting in octahedral geometry towards Co(II) and Zr(IV) complexes, and square planer geometry towards Ni(II) metal ion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This outcome agrees with the FMO idea of the electron density distribution. From the above, it may be concluded that a compound's biological activity can be described by its quantum chemical properties, which are confirmed by MEPs 40,106 …”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…This outcome agrees with the FMO idea of the electron density distribution. From the above, it may be concluded that a compound's biological activity can be described by its quantum chemical properties, which are confirmed by MEPs 40,106 …”
Section: Resultsmentioning
confidence: 67%
“…The EI‐mass spectrum of azo‐thiosemicarbazone (H 4 Azo‐STC, 1) exhibited a precise peak corresponding to m/z 299 amu; this matches with the chemical formula (C 14 H 13 N 5 OS) and aligns well with the computed molecular weight at m/z = 299.3 amu. Furthermore, the mass spectrum exhibited several peaks associated with the progressive deterioration of the azo‐thiosemicarbazone (H 4 Azo‐STC, 1) , as observed through the fragmentation pathway illustrated in Figure S15 40 . The mass spectra of metal complexes (Figures S9–S14) revealed that the bond between metal and ligand was broken, resulting in the formation of molecular ion peaks distinct to the parent azo‐thiosemicarbazone (H 4 Azo‐STC, 1) .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations